How do corporate tax rates alter conforming tax avoidance? - Sebastian Eichfelder; Martin Jacob; Nadine Kalbitz; Kelly Wentland (Arbeitskreis Quantitative Steuerlehre (arqus), 2023)
We examine an international panel of domestic firms to quantify the degree to which conforming tax avoidance changes with statutory tax rates. We derive an alternative estimation method that identifies conforming tax avoidance from the variation of tax rates over time and across countries. We incorporate a series of validation tests by considering an alternative measure of conforming tax avoidance, investigating alternative channels for this type of tax avoidance, and showing a more pronounced response to tax rates when a country observes a significant increase in conformity between its book and tax reporting. Overall, we find a 1-percentage point decrease in the corporate tax rate corresponds with a 1.5 percent increase in pre-tax book income in domestic firms, which we interpret as a substantial conforming tax avoidance response by these firms. We also provide preliminary evidence that this type of activity plays a role in multinational firms.
Keywords: H25; H26; 330; conforming tax avoidance; tax avoidance; international tax; book-tax conformity